Penggunaan Alat Peraga Dalam Pembelajaran Tematik Untuk Meningkatkan Hasil Belajar Menulis Deskripsi Dan Operasi Bilangan Sampai 20 Pada Siswa Kelas 1 SDN 004 Rambah Samo Tahun Pelajaran 2016/2017 - Zainimar Zainimar (STKIP Rokania Pasir Pangaraian, 2018)
This research is action research which consists of planning, implementation, observation and reflection. This study consists of two cycles consisting of two meetings in each cycle. This study aims to improve the results of learning to write descriptions and number operations up to 20 students in grade 1 SDN 004 Rambah Samo academic year 2016/2017. The focus of this research is learning by using props to improve the learning result of writing description and number operation up to 20 in grade 1 student of SD Negeri 004 Rambah Samo. From result of analysis got that result of student learning have improvement of minimum mastery criteria from cycle I until cycle II that is: cycle 1 (42%) and cycle2 (87%). From the research results can be concluded that through the use of props can improve the results of learning to write descriptions and operation numbers up to 20 in grade 1 SDN 004 Rambah Samo lesson year 2016/2017